Politics of counterterrorism in India: strategic intelligence and national security in South Asia - Mahadevan, Prem (London, 2012)
in the wake of the Mumbai terrorist attacks in November 2008, terrorism and counter terrorism in India became the focus of international, regional, and national attention. Here, Prem Mahadevan, by using three case studies of Sikh separatist, Kashmiri separatist and pan-islamist groups, focuses on the efforts of India's decision-makers and intelligence agencies to create coherent and effective counter terrorism policies and actions. Questioning why Sikh separatist groups have been effectively contained, and yet pan-islamists have not, Mahadevan draws the conclusion that, due to a gap between the expectations of decision-makers and the capabilities of strategic intelligence agencies, India's ability to prevent terrorist attacks has been undermined. In addition, the role played by Pakistan's intelligence agencies in the border regions is given extensive analytical treatment. Combining a theoretical approach with empirical analysis of India's counter terrorist activities, this book holds valuable information for those examining strategy-making and counter terrorism - practitioners as well as researchers - in addition to those interested in the politics of India. .
Keywords: Counterterrorism-India